Record of New Bryophytes for Iraqi Bryoflora - B. Al-N'ima; Abdul-Huss (College of Education for Pure Sciences, 2007)
During the years (2000-20003) about (450) Specimens of have been collected from the north part of Iraq, mainly Dohuk, Erbil and Nineveh provinces. Identification revealed that they were belong to ( 40) genera and (79) species. Among them ( 4) genera and six species· (5 mosses and one liverwort) were considered new record for Iraq. Habitat of the new taxa beside their distribution in the world and Iraqi physiographic regions & districts were included in the present work.